Determinants affecting the buying of Life Insurance: A case of Kapilvastu District - Jnawali, Govind; Jaiswal, Amrita Jaiswal (Nepalese Journal of Insurance and Social Security, 2019)
This paper aims to investigate the determinants that affect the buying of life insurance in Kapilvastu district of Nepal. Primary data have been collected through structured questionnaire out of 384 life insurance policy holders resident of Kapilvastu district of Nepal. Sample was selected by purposive sampling method. The study concludes that life insurance demand in terms of premium paid is significantly associate with gender, level of education, occupation, economic class, family size and monthly income of respondents whereas life insurance demand is not significantly associated with age, religion and marital status. The study further suggests to the life insurance companies to emphasize selling of life insurance policies to the people having more income, more family members, and educated people.